2022
DOI: 10.1371/journal.pone.0266922
|View full text |Cite
|
Sign up to set email alerts
|

Effect of common maintenance drugs on the risk and severity of COVID-19 in elderly patients

Abstract: Background Maintenance drugs are used to treat chronic conditions. Several classes of maintenance drugs have attracted attention because of their potential to affect susceptibility to and severity of COVID-19. Methods Using claims data on 20% random sample of Part D Medicare enrollees from April to December 2020, we identified patients diagnosed with COVID-19. Using a nested case-control design, non-COVID-19 controls were identified by 1:5 matching on age, race, sex, dual-eligibility status, and geographical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
2
16
0
5
Order By: Relevance
“…Overall, our observation that the outpatient use of statins, ACEI/ARBs and anticoagulants were protective against adverse outcomes in patients diagnosed with COVID-19 is consistent with a review conducted by Alves et al 52 and previous studies that assessed premorbid use of these classes of cardiovascular medications. 53 , 54 , 55 , 56 , 57 It is important to note, that ours is, to our knowledge, the largest matched, national comparative analysis of cardiovascular medications and COVID-19 outcomes thus far.…”
Section: Discussionmentioning
confidence: 92%
“…Overall, our observation that the outpatient use of statins, ACEI/ARBs and anticoagulants were protective against adverse outcomes in patients diagnosed with COVID-19 is consistent with a review conducted by Alves et al 52 and previous studies that assessed premorbid use of these classes of cardiovascular medications. 53 , 54 , 55 , 56 , 57 It is important to note, that ours is, to our knowledge, the largest matched, national comparative analysis of cardiovascular medications and COVID-19 outcomes thus far.…”
Section: Discussionmentioning
confidence: 92%
“…Not all COVID-19 diagnoses are captured in Medicare claims data. Our previous study showed that up to one-third of COVID-19 cases could be missed [54]. Medicare claims-based data may miss services or treatment paid for by private insurance or other means.…”
Section: Discussionmentioning
confidence: 99%
“…Not all COVID-19 diagnoses are captured in Medicare claims data. Our previous study showed that up to one-third of COVID-19 cases could be missed [54]. Medicare claimsbased data may miss services or treatment paid for by private insurance or other means.…”
Section: Plos Medicinementioning
confidence: 99%